Diabetes, hypertension and dyslipidemia medication prescribing in Qatari primary care settings: a retrospective analysis of electronic medical records - Mohamed Ahmed Syed; Ahmed Sameer Al Nuaimi; Hamda Abdulla A/Qotba; Abduljaleel Abdullatif Zainel; Tamara Marji; Uzma Razaq (Taylor & Francis Group, 2021)
Background Globally, non-communicable diseases (NCDs) are recognised as a leading cause of morbidity and mortality. Medications and medicines optimisation play an important role in the management of modifiable physiological risk factors and NCDs. The importance of lifestyle interventions in prevention of modifiable risk factors is also well established. The aim of this paper was to describe the quantity of type 2 diabetes mellitus (T2DM), hypertension and dyslipidaemia prescribing in Qatari primary care settings. Its findings will provide necessary information to inform pharmaceutical policy and practice. Methods The study was undertaken in Qatar's publicly funded primary health care centres. Data sources for this study comprised electronic medical records. The Anatomical Therapeutic Chemical (ATC) drug classification system was used to classify the medications prescribed. The number and proportion of medications by age, sex, nationality and diagnosis (T2DM, hypertension and dyslipidaemia) were reported. Results A total 81,569 individuals were included (18-29 years 2.4%; 30-39 years 11.7%; 40-49 years 25.4%; 50-59 years 31.9% and ≥ 60 years 28.6%). 55.6% participants were male. On average 10.2 medications were prescribed per person and 2.3 medications were included in each prescription. T2DM medications were most prescribed (N = 361,87780,799; 43.2%) followed by hypertension (N = 303,086; 36.2%) and dyslipidaemia (N = 172,163; 20.5%). Of the total medications prescribed, 72% (N = 605,488) were prescribed in individuals aged 50 years and above. Men were prescribed 62% (N = 515,043) medications while women were prescribed 38% (N = 322,083) medications. Southern Asians (N = 330,338; 39%) were prescribed most medication followed by Qataris (N = 181,328; 22%) and Northern African (N = 145,577; 17%). Conclusions In Qatar's primary care settings, average medications prescribed per patients were found to be higher compared to other populations. While medications were actively prescribed for the 3 conditions, the study found variations by medication type, age, gender and nationality. Rational guidelines for the utilisation of medications need to be established with the support of real-world evidence.